Ways of Seeing, Ways of Being Seen: Josephine Baker and the Scopophilic Gaze. - Cenatiempo, Dantzel (French Historical Studies, 2023)
This article explores how Josephine Baker leveraged post–World War I European primitivism to subvert her mostly white male audience's voyeuristic gaze. Baker's youthful experiences with early twentieth‐century American minstrelsy fostered many techniques, from cross‐dressing to whiteface, that proved useful for navigating her sudden fame in Jazz Age Paris. In particular, Baker's subversive parody of her rival Mistinguett in La joie de Paris in 1932 demonstrates how skin color, despite becoming both fetish and fashion during the interwar period, still fell into colonial hierarchies. Baker used her body to resist this system, moving away from her two‐dimensional public image as a nude banana dancer and closer to the World War II agent and antisegregation activist she would soon become. The theories of Sigmund Freud, Frantz Fanon, Joanne B. Eicher, and Laura Mulvey help elucidate how this 1932 performance, by destabilizing gendered and racialized stereotypes, marks a significant turning point in Baker's political consciousness.